Bubaline alphaherpesvirus 1 induces a latent/reactivable infection in goats. (February 2019) - Camero, M.; Lanave, G.; Lucente, M.S.; Losurdo, M.; Di Paola, G.; Lorusso, E.; Martella, V.; Buonavoglia, C.; Tempesta, M.
Highlights: Bubaline herpesvirus 1 (BuHV-1) was detected in trigeminal ganglia of experimentally infected goats. Latent infection was reactivated with desamethasone in a goat 10 months after the experimental infection. The reactivated virus was shed through nasal and ocular secretions. Reactivation of BuHV-1 in goat resulted in a 4-fold increase in the antibody titer. Abstract: Latent infection is a common mechanism used by several alphaherpesviruses to persist in their host but it is not clear whether this mechanism is also triggered in heterologous infections. Cross-species infections have been documented repeatedly for alphaherpesviruses of ruminants, a group of closely related viruses. Herewith we report latent infection with bubaline alphaherpesvirus 1 (BuHV-1) in experimentally infected goats and subsequent virus reactivation after treatment with dexamethasone (DMS) at 10 months after infection. After DMS treatment, the virus was isolated in one such animal in the nasal swabs from day 3 to 9 post treatment and in the ocular swabs at day 6. The goat was euthanized 48 days after DMS treatment and viral DNA was detected by PCR in the trigeminal ganglia and in two cervical ganglia. Additionally, BuHV-1 DNA was detected by PCR in the trigeminal ganglia of the other 3 goats.